2020
DOI: 10.1017/s1041610220001258
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 health worries and anxiety symptoms among older adults: the moderating role of ageism

Abstract: ABSTRACT A prominent feature of anxiety in late life is concerns regarding physical health. Anxiety symptoms among older adults have been connected with various psychological outcomes, including social isolation and loneliness. During the coronavirus disease 2019 (COVID-19) pandemic, many societies have demonstrated increased ageist attitudes, encouraging older adults to distance themselves from society. Accordingly, the current study examined the moderating role of COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
124
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 128 publications
(142 citation statements)
references
References 10 publications
10
124
1
7
Order By: Relevance
“…Examining ambivalent ageism was important given the well-intentioned, yet patronizing messages that all older adults must be cared for and protected during the pandemic, without recognition of the diversity of older adults. Ageism during COVID-19 is reflected in studies reporting that older adults with more negative perceptions of aging report greater loneliness and distress during lockdown (Losada-Baltar et al, 2020), and older adults' ageist attitudes moderate the relationship between health anxiety and general anxiety (Bergman et al, 2020). That benevolent, not hostile, ageism was associated with greater worry about COVID-19 is a unique addition to the growing literature on ageism in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining ambivalent ageism was important given the well-intentioned, yet patronizing messages that all older adults must be cared for and protected during the pandemic, without recognition of the diversity of older adults. Ageism during COVID-19 is reflected in studies reporting that older adults with more negative perceptions of aging report greater loneliness and distress during lockdown (Losada-Baltar et al, 2020), and older adults' ageist attitudes moderate the relationship between health anxiety and general anxiety (Bergman et al, 2020). That benevolent, not hostile, ageism was associated with greater worry about COVID-19 is a unique addition to the growing literature on ageism in the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Indicators of mental health (depression, anxiety, and health anxiety) were included, as those with higher levels of psychological symptoms report more negative responses to the pandemic (e.g. Bergman, Cohen-Fridel, Shrira, Bodner, & Palgi, 2020;Huang & Zhao, 2020;Losada-Baltar et al, 2020). Therefore, in this study, we expected individuals who report greater anxiety, depression, and health anxiety to also indicate greater COVID-19 worry.…”
mentioning
confidence: 99%
“…Our results are in line with recently published studies on COVID-19, indicating that older people demonstrated less negative emotions and anxiety/depression symptoms than younger cohorts (Bruine de Bruin, 2020), and that well-being in the older cohorts is not compromised by COVID-19 (L opez et al, 2020). Negative emotional responses to the pandemic are likely to be moderated by factors others than age, such as personality, ageism, and family functioning (Bacon & Corr, 2020;Bergman et al, 2020;L opez et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that old-old adults showed a level of well-being comparable to the one of young-old adults, suggesting that people in late adulthood have personal resources and effective regulation strategies to cope with the situation. Also, Bergman, Cohen-Fridel, Shrira, Bodner, and Palgi (2020) investigated COVID-related ageism, which is the prejudicial view that the pandemic is an "older adults' problem", and consequently they have to be isolated from the society. The authors found that COVID-related ageism moderated the link between worries about the pandemic and anxiety symptoms, revealing that older adults with higher levels of ageism were more at risk of anxiety symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Using a 5-point scale (0 = not at all to 4 = extremely ), survivors completed the severity of symptoms during the last few weeks while referring to the Holocaust while comparisons referred to the most traumatic event they have experienced (α = 0.73). Respondents also completed five items regarding COVID-19 worries ( Bergman et al, 2020 ), and the three items from the UCLA Loneliness Scale ( Hughes et al, 2004 ), using a 5-point scale in both scales (0 = not at all to 4 = almost always ) (α = 0.86 and 0.91 for COVID-19 worries and loneliness, respectively).…”
Section: Methodsmentioning
confidence: 99%